Incidence, Temporal Trends, and Socioeconomic Aspects of Acquired Male Hypogonadism - Percik, Ruth; Vered, Shiraz; Liel, Yair (Experimental and Clinical Endocrinology & Diabetes, 2025)
Little is known about temporal trends in the incidence of male hypogonadism and its correlation with socioeconomic status, which we examined in the present study.Data were extracted from the Maccabi Health Services computerized database between 2001–2017. The study population included 4,261 men aged 21 to 80 years with biochemically proven hypogonadism defined and classified according to the European Male Aging Study criteria. Patients on testosterone or testosterone-modifying drugs were excluded. The socioeconomic status was assessed based on verified financial data pertinent to the area of residence.The incidence of male hypogonadism increased with age in all the socioeconomic strata. Among the hypogonadal men, 75% had hypogonadotropic hypogonadism. The overall incidence of hypogonadism increased 1.4-fold between the 2001–2009 and 2010–2017 periods [from 41.7 (39.7–43.8) to 58.5 (56.4–60.8) per 100,000 person-years) (95% CI)], mainly due to an increase in hypogonadotropic hypogonadism. The temporal increase in hypogonadotropic hypogonadism occurred in all age groups and all socioeconomic strata but was notably more prominent in >51-year age groups of the more affluent socioeconomic strata. The mean body mass index remained unchanged throughout the study period.A temporal increase was observed in male hypogonadism, mainly hypogonadotropic hypogonadism, corresponding with previously observed temporal decreases in testosterone levels in men. This trend could be possibly partly attributed to an underappreciated increase in mental distress due to decreasing global happiness indices, increasing stress, and occupational burnout in specific occupations associated with more affluent populations (i.e., high-tech, finance, medical). This preliminary proposition deserves further investigation.
Keywords: Insufficiencies; Hypopituitarism; Hormones; Luteinizing hormone; Follicle-stimulating hormone; Cardiovascular incidences; Cardiovascular risk management; Gonadotrophins